Nanosized TiO2 Photocatalyst Powder via Sol-Gel Method: Effect of Hydrolysis Degree on Powder Properties - Nor Hafizah; Iis Sopyan (International Journal of Photoenergy)
Nanosized TiO2 powder was synthesized via sol-gel method using titanium tetraisopoxide (TPT) as the precursor. Mol ratios of water to TPT were varied from 1 (Powder A), 2 (Powder B), 3 (Powder C), and 4 (Powder D) to evaluate effect of hydrolysis degree. TG/DTA curves showed that amorphous phase turned to anatase crystal structure at ca. 415, 337, 310, and 339∘C for Powders A, B, C, and D, respectively. XRD analysis showed that all the synthesized TiO2 powders were 100% in anatase form with Powders B and C showing considerably higher crystallinities. The powders obtained at lower water to TPT mol ratios were spherical in shape and they became bar-like shapes higher mol ratios. The lower hydrolysis degree led to higher surface area of the Powder A (24.8 m2/g) compared to Powder B (14.6 m2/g). From phenol photocatalytic measurement, Powder B was the most efficient attributed to its higher crystallinity.